Scarlett : The Sequel to Margaret Mitchell's Gone With the Wind - Ripley, Alexandra (London Pan Books, 1992)
The sequel to Margaret Mitchell's Gone with the wind.
Keywords: Ireland -- O'Hara, Scarlett (Fictitious character) -- Americans